Analysis of Writing Patterns of Letters O, D, and Y as Considerations for the Criteria of Developing Indonesian Language Teaching Materials - Hamdani; Neneng Nendah Nurhamidah; Munah Widiawati (Studies in Learning and Teaching, 2023)
Teaching materials may be considered to be effective if their preparation is adjusted to the level of students’ internal potential and cognitive abilities. Therefore, graphology is required to assist in identifying students’ inner potential for the results of the graphological analysis to be used as a basis for preparing materials. This research aims to discover students’ inner potentials using graphological sciences, which can later be used to consider the criteria for preparing teaching materials. This research used a descriptive qualitative research method since this research produces data in the form of descriptive data (writing). The research’s subject is the handwriting of students of X-1 class Bekasi Regency. The stages of this research are handwriting analysis, triangulation through interviews, grouping results. The data used is in the form of student handwriting with an assessment of the characteristics of student writing as a whole in terms of the slope of writing, the direction of the writing line, the size of the writing, the spacing between words, and the spacing between lines. Qualitative research data analysis techniques are carried out with the stages of analysis implementation according to Miles and Huberman with stages: (1) Data reduction, (2) Presentation of data; (3) Drawing conclusions. According to the study’s result, it was discovered that the students’ inner potentials were very diverse. As a result, the form in which teaching materials are prepared must likewise be varied.